Corruption from a regulatory perspective - Benedetto, Maria De (London [England] : Hart Publishing, 2021)
"This book seeks to challenge and, in some cases, reverse current ideas on corruption and its prevention. It is a long held belief that sanctions are the best guard against corrupt practise. This innovative work argues that in some cases sanctions serve to increase corruption: arguing that they provide an opportunity for corrupt transactions in their flouting. Instead it suggests that better regulation, not sanctions, offers the most effective response to corruption. Taking both a theoretical and applied approach, it examines the question from a global perspective, drawing on in particular economic approaches, to provide a model for tackling corrupt practises."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Corruption -- Law and legislation; Political corruption -- Prevention; Corruption -- Prevention; Law; Electronic books